Analyzing pregnancy course and outcomes in women with varying degrees of severity of novel coronavirus infection COVID-19 in Saint Petersburg: the lessons from pandemic - V. F. Bezhenar; M. L. Romanova; I. M. Nesterov; I. A. Dobrovolskaya (Акушерство, гинекология и репродукция)
Introduction. Today, two years after the first outbreak of the novel coronavirus infection (NCI) COVID-19, there is still insufficient data to fully assess risks and pattern of the course of this infectious disease in pregnant women.Aim: to conduct a comparative analysis of perinatal pregnancy outcomes as well as clinical and laboratory data in COVID-19 patients at the time of delivery and those suffering from the disease during pregnancy.Materials and Methods. A retrospective comparative study was carried out after analyzing pregnancy and childbirth histories in 191 women admitted for delivery in three obstetric medical organizations of Saint Petersburg in the years 2020–2021. Perinatal outcomes of pregnancy as well as clinical and laboratory data in patients suffering from COVID-19 during pregnancy were analyzed: Group 1 – 57 patients with asymptomatic and mild form of verified COVID-19; Group 2 – 50 patients with COVID-19 of moderate and severe course; Group 3 – 52 patients who underwent COVID-19 in the third trimester of pregnancy. Group 4 (control) consisted of 32 women lacking COVID-19.Results. Comparing delivery outcomes in Group 1 vs. Group 2 revealed a significantly higher rate of urgent deliveries – 54 (94.7 %) and 38 (76.0 %) (χ2 = 7.76) respectively, as well as a significantly lower number of premature births – 3 (5.3 %) and 12 (24.0 %) (χ2 = 7.76) respectively. Comparison of Group 1 vs. Group 3 showed significantly fewer natural births – 33 (57.8 %) and 42 (80.8 %) (χ2 = 6.63) respectively, but a greater rate of caesarean section – 24 (42.0 %) and 10 (19.2 %) (χ2 = 6.63). Comparison of Group 1 vs. Group 4 revealed a significantly higher number of women with acute and progressive fetal hypoxia (fetal distress) – 16 (28.1 %) and 2 (6.3 %) (χ2 = 6.05) respectively. These data allow us to state about an impact of the severity of infectious process SARS-CoV-2-caused disease and its timeframe during pregnancy on the timing and method of delivery. No significant data were obtained that might allow to state that the infectious process directly caused increased rate of premature birth in pregnant women with moderate and severe COVID-19. At hospital admission and discharge, patients with mild and asymptomatic COVID-19 were significantly less likely to have neutrophilia – 5 (8.8%) and 42 (84.0%) (χ2 = 61.2; p < 0.001) respectively, increased aspartate aminotransferase – 4 (7.0 %) and 38 (76.0 %) (χ2 = 53.15; p < 0.001), lactate dehydrogenase (LDH) – 0 (0.0 %) and 12 (24.0 %) (χ2 = 15.41; p < 0.001), C-reactive protein (CRP) – 6 (10.5 %) and 49 (98.0 %) (χ2 = 81.58; p < 0.001), creatinine reduction – 0 (0.0 %) and 11 (22.0 %) (χ2 = 13.98; p < 0.001) respectively. In groups with severe, mild and asymptomatic COVID-19, a strong direct correlation was established the CRP level and leukocyte count, between level of serum CRP and alanine aminotransferase; a less noticeable relationship was observed between serum CRP and LDH concentrations, CRP and total protein level.Conclusion. It was shown that no specific effect of SARS-CoV-2 infection was exerted on majority of parameters related to normal course of labor, as well as on condition of neonates born to patients with COVID-19 of varying severity. In patients with COVID-19 at the time of delivery, changes in clinical and laboratory parameters corresponded to the disease severity.